The Web Interface Should Be Radically Refactored - Douceur, John (JD); Howell, Jon; Parno, Bryan; Walfish, Michael; Xiong, Xi (Tenth ACM Workshop on Hot Topics in Networks (HotNets-X), 2011)
The Web API conflates two conflicting goals: serving developers by supporting a wide and growing suite of functionality, and providing applications with an isolated execution environment. We propose to split the API into two levels of interface: a low-level interface that governs the relationship between the application and the browser, and a set of high-level interfaces that govern the relationship between the application and its developer. We delineate a tiny set of properties needed by the low-level interface. We argue that this restructuring provides significant benefit to both developers and users.